Acute formaldehyde exposure induced early Alzheimer-like changes in mouse brain. (12th February 2018) - Liu, Xudong; Zhang, Yuchao; Wu, Ruliu; Ye, Meng; Zhao, Yuqing; Kang, Jun; Ma, Ping; Li, Jinquan; Yang, Xu
Abstract: Alzheimer's disease (AD) is a serious, common, global disease, yet its etiology and pathogenesis are incompletely understood. Although an association between AD and exposure to air pollutants has been discussed, the effects of pollutants on the functioning of the brain remain unclear. The indoor environment is where exposure to formaldehyde (FA) can occur. Whether exposure to FA contributes to the development of AD needs to be investigated. To determine the objective, C57BL/6 mice were exposed daily to FA (0, 0.155, 1.55 and 15.5 mg/kg/day) for 1 week. After acute FA exposure, some early AD-like changes [cognitive deficits, pathological alterations in the mouse brain, accumulation of total β-amyloid plaques 1-42 (Aβ1-42 ) and hyper-phosphorylated tau (Tau-P) in the cerebral cortex] were detected after exposure to high concentrations of FA (1.55 or 15.5 mg/kg/day). The permeability of the blood–brain barrier (BBB), activation of astrocyte and microglia, oxidative stress (OS) and inflammation were analyzed to explore the toxicity mechanisms behind the development of early AD-like changes. While exposed to a low concentration of FA (0.155 mg/kg/day) had little or no adverse effects on the mouse brain. The results indicated that acute FA exposure induced early AD-like changes in mouse brain, increased the susceptibility of AD in mouse.